Sejarah Pembentukan Gerakan Pramuka Dan Pengaruhnya Dalam Dunia Pendidikan Islam - Lutfiasin Lutfiasin (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2021)
In an effort to reconstruct past events that occurred once in human life and analyze their influence on Islamic education, in this case the life of a character and his role in people's lives as well as knowing the resulting influence in the world of Islamic education. So this study uses a historical approach, historical methods and qualitative descriptive analysis of the object of discussion by utilizing reference sources on related themes and using library research methods. By using this approach, researchers can uncover historical facts about the role of Sri Sultan Hamengkubuwono IX in the formation of the Scout Movement in 1960-1961 AD and the resulting influence in the world of Islamic education. This historical research and analysis is intended to make a systematic and objective reconstruction of the past, by collecting, evaluating, verifying and synthesizing evidence to support the facts in obtaining strong conclusions and analyzing the literature. Researchers explore and collect data related to the discussion of this research. The results of this study are: 1. Sri Sultan Hamengkubuwono IX has a very important role in the formation and development of the scout movement so that he is trusted to serve as chairman of the Scout Movement Quarter and has been named the FATHER of Scouting because of his services and thoughts on the Scouting Movement. 2. The Scout Movement has a positive influence in the world of Islamic education, especially in the formation of morals